Kerajaan-Oriented Islam: The Experience of Pre-Colonial Indonesia - Burhanudin, Jajat (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2006)
These two texts, al-Mawahib and Taj us-Salatin, further had similarities in terms of both language and their substances. In this paper, al-Mawahib will be discussed in its relation to Taj us-Salatin. But before we come to the discussion, the author will pay attention to several texts which preceded al-Mawahib in creating the initial discourse on Islamic politics. As the author will show below, both al-Mawahib and Taj us-Salatin contributed to shaping Islamic political ideas in the land below the wind, that is, what are now referred to as Indonesia and Malaysia.DOI:Â 10.15408/sdi.v13i1.575